CEFR Pada Materi Bahasa Arab: Inovasi Pembelajaran Ramah Anak Pada Sekolah Dasar - Hidayah, Nurul; Mukmin; Cardasyifa (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Learning Arabic as a foreign language is best started at an early age, but unfortunately not all schools include Arabic teaching materials in their curriculum. Whereas Arabic is one of the foreign languages whose vocabulary is widely absorbed in Indonesian, it's just that students are not much accustomed to hearing and even using it in conversation, CEFR tries to unravel this as a solution to make learning Arabic fun.The purpose of this study is to test the effectiveness of CEFR as a child-friendly learning innovation in elementary schools. The research method used was mixed method with sequential explanatory type The result showed that this treatment has effectiveness on students' ability to speak Arabic on al-mihnah material. Through this learning, students not only become brave to express themselves in Arabic but also happier because they learn according to their own abilities and learning styles without having to be forced to memorize at the end of the learning meeting.